(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This historical study focuses on the life, contributions, and legacy of Thyaaki P.S. Mony, a significant figure whose actions, beliefs, and influence shaped his era. Through a detailed examination of primary sources, archival materials, and secondary literature, the study explores his socio-political involvement, key achievements, and the broader historical context in which he lived. The research also delves into the impact of his work on the development of local or regional movements, addressing the socio-cultural and economic conditions of the time. By evaluating his interactions with contemporaries and the lasting effects of his ideas, this study offers new insights into the historical period, enriching our understanding of the historical landscape. The study concludes by assessing the enduring relevance of Thyaaki P.S. Mony’s legacy in modern contexts, offering a deeper appreciation of his contributions to history.